The Effect Of Using Frank Lester’s Strategy In The Geometric Thinking Skills Of The Second Grade Intermediate School Female Students In Mathematics - Salal Al-Shouaily, Noor Rahmaan; Abd Al-Amer, Abbas Naji (Opción, 2019)
The present research aims to identify the effect of using the strategy of Frank Lester in the skills of engineering thinking (visual, logical, applied) among second graders in mathematics. To verify the research objective, the following hypothesis was developed: “There is no statistically significant difference at the level of (0.05) between the average scores of students studying according to Frank Lester’s strategy and the average scores of students studying according to the usual method of teaching the test of engineering thinking skills (visual, logical, applied).”